Evaluation of geotechnical properties of gully erosion materials in ORLU and its environs, IMO state, Nigeria - O.K, Iheme; V.U., Okoye; A.I., Chinwuko; A.O., Usman; C.F., Ejeke; C.E, Osele (International Journal of Advanced Geosciences, 2016)
The evaluation of geotechnical properties of rock materials is used to ascertain the environmental factor that necessitated gully erosion in Orlu and its environs, Imo State, Nigeria. The study is aimed at geotechnically defining the characteristics, causes and formation of the gully erosion with particular emphasis on the current land degradation in the study area. Data used in the study were derived from field measurements, and laboratory analysis. Gully variables such as length, depth and widths were also determined. The result of the geological mapping revealed that there are three geologic formations encountered in the study area namely; Ameki, Ogwashi Asaba, and Benin Formations. The result of the field studies shows that 27% of the gullies observed occur in Ameki Formation while no gully was discovered in Ogwashi Asaba formation. The grain size distribution curves interpretation revealed that 80% (by weight) of the soils are medium to coarse grained sand and fine gravels, while the remaining 18% and 2% are for fine grained sand and coarse grained silt. The Atterberg Limit Test interpretation shows that the plasticity index of the formations ranges from 24.83% to 48.42%. Based on the results of the geotechnical properties of rock materials in the study area, the factors responsible for gullies occurrence in the study area were identified as topography, rainfall, geology, and anthropogenic factors. The devastating effects of gully erosion in the study area were observed to include loss of about 22km2 of arable lands; 2 major and 6 minor road failures; loss of many houses and other infrastructures; pollution of surface and underground water. Finally, it is recommended that the appropriate authorities, individuals and all stakeholders in the environmental protection agency should develop ideas in environment watch towards gully erosion control.